Increased serum levels of vascular endothelial growth factor in pemphigus foliaceus patients with erythroderma. (26th August 2016) - Miyamoto, D.; Sotto, M.N.; Otani, C.S.V.; Fukumori, L.M.I.; Pereira, N.V.; Santi, C.G.; Maruta, C.W.; Burnier, M.N.N.; Rebeis, M.M.; Aoki, V.
Abstract: Background: Erythroderma is a clinical skin syndrome shared by patients with cutaneous disorders of distinct aetiologies as a result of the combined actions of chemokines, adhesion molecules, and cytokines, such as vascular endothelial growth factor (VEGF). Objective: To evaluate the profile of serum levels of VEGF and soluble vascular endothelial growth factor receptor 1 (sVEGFR‐1) in pemphigus foliaceus (PF) patients with erythroderma. Methods: We conducted a retrospective study, which included (i) a chart review of all PF patients from the Autoimmune Blistering Clinic, University of Sao Paulo, Brazil, from January 1991 to December 2014, together with an evaluation of demographic variables, hospitalization duration and complications and (ii) analysis of the circulating VEGF and sVEGFR‐1 levels in PF patients with erythroderma by ELISA. The controls included patients with pemphigus vulgaris or psoriasis. Results: We observed higher serum VEGF levels in PF patients during erythroderma than during the non‐erythrodermic phase. PF patients showed increased serum levels of sVEGFR‐1 during the erythrodermic phase in comparison to controls. Interestingly, the sVEGFR‐1 and antidesmoglein‐1 levels were positively correlated during the non‐erythrodermic period. Conclusion: Erythroderma, which represents one clinical form of PF, implies more severe outcomes. The circulating levels of VEGF, a potent endothelial activator, are increased in PF patients with erythroderma; this result suggests the contribution of the blood vessel endothelium to the pathogenesis of this clinical syndrome. Interestingly, our findings showed a positive correlation between the sVEGFR‐1 and antidesmoglein‐1 antibody levels, indicating a suppressive response to VEGF augmentation during the erythrodermic phase of PF.